2021
DOI: 10.1111/bjh.17817
|View full text |Cite
|
Sign up to set email alerts
|

Allogeneic hematopoietic cell transplantation in patients with myelodysplastic syndrome using treosulfan based compared to other reduced‐intensity or myeloablative conditioning regimens. A report of the chronic malignancies working party of the EBMT

Abstract: Allogeneic haematopoietic-cell transplantation (allo-HCT) is a potentially curative therapy for high-risk myelodysplastic syndrome (MDS). Reducedintensity conditioning (RIC) is usually associated with lower non-relapse mortality (NRM), higher relapse rate and similar overall-survival (OS) as myeloablative-conditioning (MAC). Fludarabine/treosulfan (FT) is a reduced-toxicity regimen with intense anti-leukaemia activity and a favourable toxicity profile. We investigated post-transplant outcomes in 1722 MDS patie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 40 publications
1
7
0
Order By: Relevance
“…In addition, early studies suggested that a high-intensity myeloablative conditioning (MAC) regimen should be considered whenever clinically suitable as the risk of MDS relapse after Allo-HCT in the HMA-exposed is higher in patients who receive lower-intensity conditioning (HR 1.81, 95% CI 1.07–3.06, p = 0.03) [ 88 ]. Yet, recent evidence suggests that a lower-intensity regimen of Fludrabine/Treosulfan (FT) possesses survival advantages over MAC or other reduced-intensity conditioning (RIC) regimens [ 89 ]. A comparison of the three types of conditioning regimens suggested indeed that FT was associated with a lower relapse risk than RIC (HR 0.55, 95% CI 0.42–0.73, p < 0.001), in a similar fashion to MAC (HR 0.61, 95% CI 0.28–0.77, p < 0.001) [ 89 ].…”
Section: Management Of Patients After Hma Failurementioning
confidence: 99%
See 2 more Smart Citations
“…In addition, early studies suggested that a high-intensity myeloablative conditioning (MAC) regimen should be considered whenever clinically suitable as the risk of MDS relapse after Allo-HCT in the HMA-exposed is higher in patients who receive lower-intensity conditioning (HR 1.81, 95% CI 1.07–3.06, p = 0.03) [ 88 ]. Yet, recent evidence suggests that a lower-intensity regimen of Fludrabine/Treosulfan (FT) possesses survival advantages over MAC or other reduced-intensity conditioning (RIC) regimens [ 89 ]. A comparison of the three types of conditioning regimens suggested indeed that FT was associated with a lower relapse risk than RIC (HR 0.55, 95% CI 0.42–0.73, p < 0.001), in a similar fashion to MAC (HR 0.61, 95% CI 0.28–0.77, p < 0.001) [ 89 ].…”
Section: Management Of Patients After Hma Failurementioning
confidence: 99%
“…Yet, recent evidence suggests that a lower-intensity regimen of Fludrabine/Treosulfan (FT) possesses survival advantages over MAC or other reduced-intensity conditioning (RIC) regimens [ 89 ]. A comparison of the three types of conditioning regimens suggested indeed that FT was associated with a lower relapse risk than RIC (HR 0.55, 95% CI 0.42–0.73, p < 0.001), in a similar fashion to MAC (HR 0.61, 95% CI 0.28–0.77, p < 0.001) [ 89 ]. In contrast, patients receiving MAC had higher nonrelapse mortality (NRM) when compared to RIC (HR 1.44, 95% CI 1.15–1.8, p = 0.001) and FT, which had a similar NRM risk to RIC (HR 0.88, 95% CI 0.67–1.15, p = 0.35) [ 89 ].…”
Section: Management Of Patients After Hma Failurementioning
confidence: 99%
See 1 more Smart Citation
“…Due to its presumed more favorable organ toxicity profile, treosulfan has been incorporated in conditioning regimens for allo‐HSCT. A retrospective study from the EBMT registry for MDS patients showed that treosulfan in combination with fludarabine (Tre/Flu) was associated with lower risk of relapse (HR 0.55; p < .001) and higher OS (HR 0.72; p = .01) when compared with other MAC and other RIC regimens 45 . Recently, a phase III randomized study was published, which compared RIC Tre/Flu and Flu/Bu2 RIC regimen for AML/MDS patients, 50–70 years or younger patients with significant comorbidities (HCT‐CI >2).…”
Section: Conditioning Regimens For Transplantationmentioning
confidence: 99%
“…Shimoni et al . build on the existing literature to specifically describe outcomes in patients with MDS comparing FT with other RIC and MAC regimens 11 . In their analysis they confirm that FT has comparable non‐relapse mortality (NRM) to RIC regimens but at the same time less risk of relapse compared to both RIC and MAC regimens resulting in an improved OS.…”
mentioning
confidence: 91%